주의력결핍 과잉행동장애 아동에서 공존질환에 따른 OROS-Methylphenidate의 효과와 안전성 - 윤형준; 육기환; 전덕인; 석정호; 홍나래; 조성식; 홍현주; Yoon, Hyung-Jun; Yook, Ki-Hwan; Jon, Duk-In; Seok, Jeong-Ho; Hong, Na-Rei; et al. (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2008)
Objectives: The purpose of this study was to evaluate the efficacy and tolerability of osmotic release oral system-methylphenidate (OROS-MPH) in children with attention-deficit hyperactivity disorder (ADHD) and comorbid psychiatric disorders. Methods: This was an 8-week open label study of OROS-MPH monotherapy. The subjects were 113 children with ADHD aged 6-12 years. Outcome measures were the Korean version of the parent ADHD Rating Scale (K-ARS), Korean version of the Conners Parent Rating Scale (K-CPRS), Clinical Global Impression-Severity and Clinical Global Impression-Improvement. Side effects were monitored using Barkley's Side Effect Rating Scale. We compared the change-over-time in the mean scores of the outcome measure according to the comorbidity of disruptive behavior disorder, depressive disorder, anxiety disorder, and tic disorder. Results: The mean K-ARS and K-CPRS scores were significantly decreased, regardless of the comorbidity. The mean doses of OROS-MPH and dropout rate did not differ significantly according to comorbidity. The OROS-MPH was well tolerated, regardless of the comorbidity. However, children with tic disorder reported a higher frequency of tics or nervous movements between the $2^{nd}\;and\;8^{th}$ week than those without tic disorder. Conclusion: The OROS-MPH is effective for decreasing the symptoms of ADHD, and it is well tolerated, even by patients with comorbid psychiatric disorders.